2023
DOI: 10.1002/cm.21740
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and divergence of the G‐interfaces of Drosophila melanogaster septins

Abstract: Septins possess a conserved guanine nucleotide‐binding (G) domain that participates in the stabilization of organized hetero‐oligomeric complexes which assemble into filaments, rings and network‐like structures. The fruit fly, Drosophila melanogaster, has five such septin genes encoding Sep1, Sep2, Sep4, Sep5 and Pnut. Here, we report the crystal structure of the heterodimer formed between the G‐domains of Sep1 and Sep2, the first from an insect to be described to date. A G‐interface stabilizes the dimer (in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 71 publications
3
12
0
Order By: Relevance
“…With a classic septin fold based on a three layered αβα sandwich (Fig. 2) (Cavini et al, 2021), we observed that Cdc3G, Cdc10G and Cdc10 ∆1-10 are all very similar to other septin structures already described in other species (de Freitas Fernandes et al, 2022;Mendonça et al, 2021;Rosa et al, 2020), reinforcing that many of the structural characteristics are highly conserved.…”
Section: Overall Description and Interface Arrangements Within The Cr...supporting
confidence: 76%
See 4 more Smart Citations
“…With a classic septin fold based on a three layered αβα sandwich (Fig. 2) (Cavini et al, 2021), we observed that Cdc3G, Cdc10G and Cdc10 ∆1-10 are all very similar to other septin structures already described in other species (de Freitas Fernandes et al, 2022;Mendonça et al, 2021;Rosa et al, 2020), reinforcing that many of the structural characteristics are highly conserved.…”
Section: Overall Description and Interface Arrangements Within The Cr...supporting
confidence: 76%
“…S2A) confirms the co-purification of Cdc3G-Cdc10G, demonstrating the positive influence of the correct G-interface partner (Cdc3) on the stability and solubility of Cdc10 (as has also been observed for their full-length versions (Baur et al, 2019)). In addition, the absence of the N-and C-terminal domains suggests that complex formation via the G-interface is viable as reported for septins from other organisms (de Freitas Fernandes et al, 2022;Rosa et al, 2020). The SEC profile shows two oligomeric states in solution (Fig.…”
Section: Protein Purification and Oligomeric State Characterizationsupporting
confidence: 55%
See 3 more Smart Citations